The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/1096348020926546
|View full text |Cite
|
Sign up to set email alerts
|

Active Sport Tourism in Europe: Applying Market Segmentation Model Based on Human Values

Abstract: The purpose of this study was to examine if human values sets indicating basic motivational aspects, shared by active sport participants, could be used for the creation of a specific market segmentation model. While the exploration of motivation scales and sport tourist typologies was vast, although limited to small samples, this research constructed a model that tested its applicability and validity on the large general samples. By using data collections from the European Social Survey, the model allowed comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
0
12
0
2
Order By: Relevance
“…However, these data must be supplemented and confronted with data from related scientific disciplines, including analyses of trends in youth PA preferences. Terzić et al pointed out the lack of information on tourism preferences of tourists within Europe, as well as the importance of monitoring changes in preferences of sport participants for specific marketing strategies [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these data must be supplemented and confronted with data from related scientific disciplines, including analyses of trends in youth PA preferences. Terzić et al pointed out the lack of information on tourism preferences of tourists within Europe, as well as the importance of monitoring changes in preferences of sport participants for specific marketing strategies [26].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, part of the clientele from these countries will reject certain sports activities due to a lack of information but will accept habitual physical activities. We assume that the proposed model of tourism strategy focusing on PA could, in addition to economic [70], geopolitical [71], social cognition [72], active sport [26], active outdoor sport event tourism [27], and other models, expand the appropriate business strategy choices in tourism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic human value sets determine motivation and can be employed to predict general travel behavior, destination choices, leisure activities, preferences, trip length, etc. (Salim Saji et al, 2015;Terzi c et al, 2021). Aebli et al (2022) use Herzberg's theory of motivation to consider tourists' needs and observed risks as opposing sets of psychological factors shaping travel willingness during and after the COVID-19 pandemic.…”
Section: Personality and Human Valuesmentioning
confidence: 99%
“…Prior research on AST behavioral intention has been linked with an event per se, along with destination attributes, nostalgia, service quality, and inspiration sources (Newland and Yoo, 2021;Zhou et al, 2018). Several researchers in AST focused on developing motivation scales and typologies to segment active sports tourists (Terzi c et al, 2020;Geffroy, 2017;Hodeck and Hovemann, 2016;Hungenberg et al, 2016). Other studies have emphasized the impact of cultural influences on tourist behavior (Tomik et al, 2017;Hungenberg et al, 2016;Reynolds and Hritz, 2012;Papadimitriou and Gibson, 2008;Williams and Gibson, 2004).…”
Section: Introductionmentioning
confidence: 99%